On some families of subsemigroups of a numerical semigroup (2020)
To a given numerical semigroup S we associate a family of subsemigroups {휕nS}, n ∈ ℕ, that permits us to understand some of the structure of S. We characterize this family in case S is a supersymmetric numerical semigroup or S has maximal embedding dimension. We also prove some properties related to embedding dimension and certain symmetry of the minimal generating set of the members of this family